Fusaric acid alters Akt and ampk signalling in c57bl/6 mice brain tissue. (April 2020) - Dhani, Shanel; Ghazi, Terisha; Nagiah, Savania; Baijnath, Sooraj; Singh, Sanil D.; Chuturgoon, Anil A.
Abstract: The brain is a highly metabolic organ and requires regulatory mechanisms to meet its high energy demand, with the PI3K/Akt and AMPK signalling pathways being central regulators of cellular energy and metabolism, also making them major targets for the development of neurometabolic disorders. Fusaric acid (FA), a toxin of fungal origin, was found to be a potent hypotensive agent in vivo and in clinical trials by altering brain neurochemistry thus demonstrating its neurological effects. Notably, FA is a putative mitochondrial toxin, however, the metabolic effects of FA in the brain remains unknown. Therefore, this study investigates the neurometabolic effects of FA via alterations to Akt and AMPK signalling pathways in C57BL/6 mice at acute (1 day) and prolonged exposure (10 days). Following 1 day exposure, FA augmented Akt signalling by increasing Akt S473 phosphorylation and the upstream regulators PI3K, mTOR and p70S6K. Activated Akt showed inhibition of GSK3 activity with the simultaneous activation of AMPK, p53 phosphorylation and reduced GLUT-1 and -4 receptor expressions, potentially suppressing neuronal glucose entry. However, after 10 days exposure, FA dampened PI3K/Akt and AMPK signalling, but increased the expression of GLUT receptors (1 and 4) in mice brain. Further, FA significantly depleted ATP levels, at 10 days exposure, despite increased PDHE1β activity (at both 1 and 10 days), strongly suggesting that FA mediates ATP depletion independent of metabolic signalling. In conclusion, FA mediates neurometabolic disturbances, at 1 and 10 day exposures, which may negatively influence normal brain aging and predispose to neurodegenerative disorders. Highlights: Exposure to fusaric acid depletes neuronal ATP levels at 1 and 10 days. Metabolic Akt and AMPK signalling pathways were activated at 1 day. Activated Akt/AMPK signalling supressed the expression of glucose receptors. At 10 days, fusaric acid dampened Akt/AMPK activity despite low ATP volume. Inactivated Akt/AMPK signalling resulted in increased glucose receptor expression.